PENGARUH HUMAN CAPITAL TERHADAP KINERJA AUDITOR PADA KAP YANG ADA DI BANDUNG - Supriatna, Nono (Jurnal Riset Akuntansi dan Keuangan, 2013)
This study is based on the importance of accountant professionalism as human capital in accounting firm as a service company. This research is intended to study the effect of human capital on the performance of auditors in KAP in Bandung by proposing research hypothesis that, human capital have positive effect on auditor performance, either partially or simultaneously. Several dimensions as sub-variables that form human caputals to be studied are represented by individual capability, individual motivation, leadership, the organizational climate, and workgroup effectiveness factors. The auditor's performance is measured by three factors that make the performance are (1) individual factors, (2) psychological factors, and (3) organizational factors. The study was conducted at an accounting firm located in Bandung. From the number of population taken random sample consisting of senior accountant and junior accountant as respondent. Data collection technique used is by using questionnaire. In accordance with the measurement scale, the data that have been collected tested the validity of Rank Spearman correlation formula and reliability with Alpha Cronbach. Data that have been tested and declared valid and reliable are then analyzed by correlation and regression analysis. Based on the results of correlation and regression analysis to test the hypothesis obtained findings of research results that human capital simultaneously have a fairly close relationship with its performance. While from multiple regression analysis it is known that each dimension gives various contribution to auditor performance and significant at p = 0,05, so from result of significance test, either partially or simultaneously can be concluded to accept research hypothesis, that is human capital have positive effect to auditor performance